Student Loans and the Dynamics of Debt - Hershbein, Brad (W.E. Upjohn Institute, 2015)
The papers included in this volume represent the most current research and knowledge available about student loans and repayment. It serves as a valuable reference for researchers and policymakers who seek a deeper understanding of how, why, and which students borrow for their postsecondary education; how this borrowing may affect later decisions; and what measures can help borrowers repay their loans successfully.